Effects of prolactin and cortisol on natural killer (NK) cell surface expression and function of human natural cytotoxicity receptors (NKp46, NKp44 and NKp30) - Mavoungou, E (Blackwell Science Inc, 2005)
The surface density of the triggering receptors (e.g. NKp46 and NKp30) responsible for natural killer (NK) cell-mediated cytotoxicity determines the ability of NK cells to kill susceptible target cells. In this study, we show that prolactin up-regulates and cortisol down-regulates the surface expression of NKp46 and NKp30. The prolactin-mediated activation and the cortisol-mediated inhibition of natural cytotoxicity receptor (NCR) surface expression reflects gene regulation at the transcriptional level. NKp46 and NKp30 are the major receptors involved in the NK-mediated killing of K562, a human chronic myelogenous leukaemia cell line. Accordingly, the prolactin dramatically increased the NK-mediated killing of the K562 cell line, whereas cortisol abolished this activity. Our data suggest a mechanism by which prolactin activates the lytic function of NK cells, and cortisol inhibits the NK-mediated attack.